(untitled) (Research, Society and Development, 2021)
The Keratoconjunctivitis sicca (KCS) or dry eye syndrome is a condition that is characterized in a qualitative and / or quantitative way, and it usually occurs in both eyes (bilateral). There are two types of treatment: medicated, which consists of using artificial tears, immunosuppressants, anti-inflammatory drugs, antibiotics; and surgical treatment in cases where there is no response after drug therapy. This work aims to seek and evaluate the treatments for dry keratoconjunctivitis in dogs that have been used in the last 15 years, as well as the efficacy of the medications and surgical techniques used, as well as to highlight the effectiveness and importance of the systematic review. Twenty-two articles were selected, of these, 17 were based on drug treatment, with immunosuppressants (tacrolimus and cyclosporine, sirolimus), topical anti-inflammatory (pimecrolimus), ethyl cyanoacrylate and a calcineurin inhibitor, and five selected studies were Surgical techniques are used, with different results efficacy. Based on the available literature and the results of the evaluation, the drugs used are effective in long-term treatments; the transplantation of salivary glands and the transplantation of mesenchymal cells have shown satisfactory results, the systematic review has the function of assisting the clinical physician in the search for new treatment alternatives.